2015
DOI: 10.1016/j.sbspro.2015.02.310
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences on Wellbeing and Quality of Life at Young Students at Psychology

Abstract: Present research is focusing on highlighting the differences between genders concerning quality of life and well-being status on undergraduate students at psychology. Participants are students ages between 19 and 22 (M=20.13; S.D.=1.038). The instruments used were: Ryff's Psychological Well-Being Scales (PWB) with 42 items distributed as Autonomy, Control, Personal Development, Positive relationships, Meaning of life, Self-acceptance and Quality of Life Scale (Flanagan, 1982). The results confirmed the gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 8 publications
1
12
1
1
Order By: Relevance
“…The analysis of the data considering the gender variable showed that the female participants had a higher score for presence of meaning in life than the male participants. This is supported by previous research by Chraif and Dumitru (2015). This indicates that female immigrants are more likely to enjoy well-being due to greater meaning in their lives.…”
supporting
confidence: 86%
“…The analysis of the data considering the gender variable showed that the female participants had a higher score for presence of meaning in life than the male participants. This is supported by previous research by Chraif and Dumitru (2015). This indicates that female immigrants are more likely to enjoy well-being due to greater meaning in their lives.…”
supporting
confidence: 86%
“…Studies on student wellbeing commonly utilized a variety of wellbeing or health measures both singularly and in combination. Wellbeing measures have included various World Health Organization (WHO) measures (Helou et al, 2019;Philippe et al, 2019), the Warwick and Edinburgh Mental Wellbeing Scale (WEMWBS; Harding et al, 2019;Kidger et al, 2019), the Positive emotion, Engagement, Relationship, Meaning and Accomplishment (PERMA) profiler (Ascenso et al, 2017;Smith et al, 2020), the Satisfaction with Life scale (Samaranayake and Fernando, 2011;Moate et al, 2019) and various versions of Ryff 's Psychological Wellbeing Scale (PWB;Chraif and Dumitru, 2015;De Clercq et al, 2019). Unidimensional mental health measures have included the Beck depression and anxiety inventories (Yazici et al, 2016;Yüksel and Bahadir-Yilmaz, 2019), the Depression Anxiety Stress scale (Koops and Kuebel, 2019), and the Kessler scale of psychological distress (K10; Brewer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Es probable que la percepción distinta respecto a las exigencias entre varones y mujeres sea la causa del comportamiento de las variables (Meisenberg & Woodley, 2015;Ozer et al, 2009). Existe evidencia de que la regulación del aprendizaje es diferente entre los géneros: las mujeres presentan puntajes más altos en responsabilidad en comparación con los hombres (Demiroren, Turan, & Oztuna, 2016) y, en lo que respecta a bienestar, las mujeres presentan valores más altos en crecimiento personal y autoaceptación, mientras que la percepción de calidad de vida es más alta en hombres (Chraif & Dumitru, 2015).…”
Section: Discussionunclassified